Bacteriological examination of drinking water supplies in Thrace - ΑΛΜΠΑΛΑΣ BEN.; ΝΑΘΑΝΑΗΛ Θ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Four hundred and forty two samples of drinking water were taken in the region of Thrace from, cities, 4 towns and 107 vilages. They were examined in situ for total coliforms and fecal coliforms, by the MPN procedure of three tubes, and for enteric pathogens (salmonellae-shigellae). One hundred and sixty two samples (36.6%) were found to contain more than 3 colonies of coliforms per 100 ml. No fecal coliforms and enteric pathogens were isolated. The need of a regular and correct chlorination of all water supplies for human use is stressed